MULTIPLE RESIDUAL ROOTS EXTRACTIONS AND ETIOPATHOGENESIS OF ASSOCIATED PERIAPICAL LESION: A SURGICAL CASE REPORT - Jesus, Oliver Renê Viana de; Alves, Rebecca Lineker da Silva; Cardoso, Allana Vieira; Santos, Juliana Maria Fernandes; Silva, Gliciane Santana da; Figueiredo, Maria Thysbe Lima de; Oliveira , Letícia de Andrade; Monteiro, Emanuele Souza; Guerra, Cecília Bezerra de Meneses Corbal (Brazilian Journal of Implantology and Health Sciences, 2024)
Before any surgical intervention in dentistry, it is necessary to plan each case correctly, to induce a positive prognosis for patients, always enabling the functionality of the stomatognathic system. Men tend to have more teeth extracted than women, with more posterior teeth extracted in patients in more advanced age groups due to periodontal disease. The case presented leads to a discussion of the periapical lesions removed surgically. The etiology and study of the evolutionary process of pulp pathology and the supporting tissues of the dental element are substantial. The endo-periodontal interrelationship is unique and can be considered a single continuous system or biological unit with multiple forms of communication. In summary, this article seeks to highlight and report a surgical case of a patient diagnosed with periapical lesions associated with residual tooth roots, which were removed during the common exodontia protocol with the aim of total rehabilitation of the patient. The patient authorized all the images and information used in this study.